COMPARISON OF POSTOPERATIVE PAIN AND HEMORRHAGE IN CHILDREN AFTER TONSILLECTOMY WITH BIPOLAR DIATHERMY TECHNIQUE VERSUS TONSILLECTOMY WITH COLD STEEL DISSECTION AND SILK LIGATURE: Pain and Hemorrhage in Children after Tonsillectomy - Khan, Muhammad Ahmed; Khan, Zafar Ullah; Akram, Sumera; Rafique, Usman; Usman, Hassan Bin (Pakistan Armed Forces Medical Journal, 2015)
Objective: To compare post operative pain and hemorrhage in children after tonsillectomy with bipolar diathermy versus tonsillectomy with cold steel dissection and silk ligation to secure hemostasis.Study Design: Randomized controlled trial.Place and Duration of Study: Combined Military Hospital (CMH) Kharian from June 2012 to June 2013.Materias and Methods: A total of 126 patients were included in the study through non-probability convenience sampling and randomly divided in two groups of 63 each.  In group A patients were treated by tonsillectomy with bipolar diathermy and in group B patients underwent tonsillectomy with cold steel dissection and silk ligation to secure hemostasis. Results in terms of postoperative hemorrhage and pain based on Facial Pain Scale were observed.Results: A total of 126 patients were included in the study and randomly divided in two groups of 63 each. Average age in group A was 6.60 years (SD ± 2.46) and in group B it was 6.31 years (SD ± 2.48). There were 33 males (52.38%) in group A while 37 males (58.73%) in group B. Both the groups are comparable with respect to gender (p=0.473) and age (p=0.522). In group A, there were 5 (7.93%) cases of mild pain as compared to 15 (23.80%) in group B. Similarly there were 32 (50.79%) cases of moderate pain in group A and 39 (61.90%) in group B. In group A 25 (39.68%) had severe pain as compared to 9 (14.28%) in group B. It indicates that patients who underwent tonsillectomy with bipolar diathermy had significantly high frequency of severe pain than group A (p=0.03). In both groups there was no incidence of primary hemorrhage. In group A, 3 (4.76%) patients had secondary hemorrhage and in group B, 1 (1.58%) patient had secondary hemorrhage however this was insignificant (p = 0.310).Conclusion: Cold steel tonsillectomy technique with silk ligation to secure hemostasis is a safe method. It has significantly less postoperative pain as compared to bipolar diathermy technique. However there is no significant difference in post operative hemorrhage between the two methods.